2012
DOI: 10.1103/physreva.85.043620
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical phases and intermittency of the dissipative quantum Ising model

Abstract: We employ the concept of a dynamical, activity order parameter to study the Ising model in a transverse magnetic field coupled to a Markovian bath. For a certain range of values of the spin-spin coupling, magnetic field and dissipation rate, we identify a first order dynamical phase transition between active and inactive dynamical phases. We demonstrate that dynamical phasecoexistence becomes manifest in an intermittent behavior of the bath quanta emission. Moreover, we establish the connection between the dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
253
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(265 citation statements)
references
References 40 publications
12
253
0
Order By: Relevance
“…This is because the laser is originally on resonance with the Rydberg transition, but the more-excited sublattice shifts the other sublattice off resonance due to the blockade effect [31]. When ∆ ∼ V , there is bistability, meaning that there are two steady states: one with low Rydberg population and one with high Rydberg population [13,14]. The intuition for bistability is as follows.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because the laser is originally on resonance with the Rydberg transition, but the more-excited sublattice shifts the other sublattice off resonance due to the blockade effect [31]. When ∆ ∼ V , there is bistability, meaning that there are two steady states: one with low Rydberg population and one with high Rydberg population [13,14]. The intuition for bistability is as follows.…”
Section: Modelmentioning
confidence: 99%
“…Figure 1 shows the mean-field phase diagram as a function of Ω and ∆, showing the antiferromagnetic and bistable regions. The phase diagram as a function of Ω and V is given in [14].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works have shown that the Rydberg interaction greatly affects how a group of atoms fluoresce [14][15][16]. When the atoms are laser excited from the ground state to a Rydberg state and spontaneously decay back to the ground state, there are strong temporal correlations between photon emissions of different atoms.…”
Section: Introductionmentioning
confidence: 99%